2021
DOI: 10.3390/ijerph18168249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-Rich Fibrin Application on Non-Infectious Complications after Surgical Extraction of Impacted Mandibular Third Molars

Abstract: Due to the frequent development of non-infectious complications after surgical removal of the third lower impacted tooth, many techniques are used to reduce their severity. Among them is the technique of applying platelet-rich fibrin to the post-extraction alveolus. The study included 90 consecutively enrolled patients. Eligible patients were randomly assigned to two groups: patients with and without platelet-rich fibrin introduced into the postoperative alveolus. Pain, swelling, trismus, and temperature were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
1
19
1
1
Order By: Relevance
“…In the studies conducted by Kumar et al [ 35 ], trismus showed a lower intensity in the group of patients in whom the alveoli were supplied with PRF in the 1st day after the surgery. Trybek et al [ 4 ] also showed better mouth opening the in group with PRF. In the study by Asutay et al [ 41 ] the effect of PRF application on the trismus was not confirmed.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the studies conducted by Kumar et al [ 35 ], trismus showed a lower intensity in the group of patients in whom the alveoli were supplied with PRF in the 1st day after the surgery. Trybek et al [ 4 ] also showed better mouth opening the in group with PRF. In the study by Asutay et al [ 41 ] the effect of PRF application on the trismus was not confirmed.…”
Section: Discussionmentioning
confidence: 95%
“…The study by Dar et al [ 36 ] showed a lower severity of pain in the group of patients in whom the alveolus was supplemented with PRF after tooth extraction, except the 14th day, when there was no significant difference. In a study by Trybek et al [ 4 ], assessing pain using the NRS scale (numerical rating scale), it was shown that after the surgery, the severity of pain was lower in the group of patients with PRF sockets filling. Ozgul et al [ 37 ] performed simultaneous extraction of both completely impacted third molars in the mandible, with similar difficulty of the procedure, by supplementing one alveolus, using PRF membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of analgesics can have a “sparing effect” such that a lower dose of the drugs can relieve pain with fewer side effects. As many nociception pathways exist in the human body, a combination of medications is recommended by the World Health Organization (WHO) [ 25 ]. NSAIDs (nonsteroidal anti-inflammatory drugs) have been shown to be effective in managing postoperative dental pain.…”
Section: Discussionmentioning
confidence: 99%